Diabetes Mellitus, Cardia and Obesity - Abstracts of Oral Presentations - Editor, The (Nepal Journal of Epidemiology, 2014)
Abstracts of the Oral Presentations at the session on Diabetes Mellitis, Cardia and Obesity at the International Conference on Research Methodology and Research Writing (ICRMSW) 2013. DOI: http://dx.doi.org/10.3126/nje.v4i2.10176